Evolution of Ecological Environment Quality in Metropolitan Suburbs and Its Interaction with Tourism Development: The Case of Huangpi District, Wuhan City - Danli Yang; Shuangyu Xie; Jianwei Sun; Huafang Qiao; Jiaxiao Feng; Xiaoyi Xie (Land)
Tourism has been a key factor in the economic growth of metropolitan suburbs. However, tourism development (TD) frequently precipitates ecological challenges, which are compounded by the absence of scientific frameworks for quantifying TD’s impact on suburban ecological environment quality (EEQ). We focused on assessing the spatiotemporal evolution of the EEQ of the primary scenic spots in Huangpi District, a suburb of Wuhan City, using a Remote Sensing Ecological Index (RSEI) model. We analyzed the impact of TD on the EEQ from 2000 to 2023 by employing independent sample t-tests, response coefficients, and the four-quadrant model. The findings indicate that the EEQ in Huangpi District from 2000 to 2023 presented the spatial distribution of “a lower EEQ in the south and a higher EEQ in the north”, first decreasing and then improving. The EEQ of the district’s scenic spots is higher than that of the entire district, and the overall trend in its variation is consistent with that for the district. TD’s impact on the EEQ in Huangpi District differs in terms of its direction and magnitude based on stage-specific characteristics, whereas for scenic spots, this difference is dependent on the grade and type of spot. We constructed a logical framework encompassing the “magnitude of difference–response characteristics–coordination status”, revealing the dynamic correlation mechanism between TD and EEQ and offering insights into balancing TD and protection of the ecological environmental, thereby facilitating the sustainable development of Huangpi District.